Os tutores da Educação a Distância: um novo profissional da educação superior brasileira - Aceti, Débora Cristina Siqueira (2012)
The present academic work aims to understand the profile of Higher Education Private Institution Distance Education tutors and their perception in relation to the meaning and importance of Higher Distance Education. It also has the purpose of identify the influence of academic background in this role. The hypothesis is that the characteristics of Distance Education tutor academic studies who teaches in Universities are insufficient as pedagogical support for this job because of the educational work with the current technological tools present in the Distance Education. The qualitative study was conducted through a questionnaire sent to 92 tutors, and a survey information was supplemented with interviews of 10 professionals in this group. The data collection aimed to reveal the composition of the group of tutors working in the institution studied. The results obtained demonstrate a prejudiced view on the Distance Education, especially in trained tutors - undergraduate or graduate - in Public Institutions. It was observed that tutors trained in the areas of exact sciences, have an understanding of education and distance education issues tied to the labor market and vocational training. We obtained a positive result demonstrating that the absence of virtual tools throughout the undergraduate or graduate, do not impede the work in this type of education, and that there is a adequacy of theoretical and practical content of these professionals to work with innovations in teaching environment and learning, as well as the importance they attach to the form the contribution of individual and social transformation of the student community